A Global Ecological Classification of Coastal Segment Units to Complement Marine Biodiversity Observation Network Assessments - Roger Sayre; Kevin Butler; Keith Van Graafeiland; Sean Breyer; Dawn Wright; Charlie Frye; Deniz Karagulle; Madeline Martin; Jill Cress; Tom Allen; Rebecca Allee; Rost Parsons; et al. (Oceanography, 2021)
A new data layer provides Coastal and Marine Ecological Classification Standard (CMECS) labels for global coastal segments at 1 km or shorter resolution. These characteristics are summarized for six US Marine Biodiversity Observation Network (MBON) sites and one MBON Pole to Pole of the Americas site in Argentina. The global coastlines CMECS classifications were produced from a partitioning of a 30 m Landsat-derived shoreline vector that was segmented into 4 million 1 km or shorter segments. Each segment was attributed with values from 10 variables that represent the ecological settings in which the coastline occurs, including properties of the adjacent water, adjacent land, and coastline itself. The 4 million segments were classified into 81,000 coastal segment units (CSUs) as unique combinations of variable classes. We summarize the process to develop the CSUs and derive summary descriptions for the seven MBON case study sites. We discuss the intended application of the new CSU data for research and management in coastal areas.